Implementation of Scrum Method on MVC-Based Sembakoqu Website - Nifea Kusumawardhani; Agung Triayudi; Benrahman Benrahman (SISFOTENIKA, 2021)
Sembakoqu is a personal online distributor website for selling various kinds of food. With prices and foodstuffs that always go up and people's purchasing power decreases because it is necessary to come to the distributor's place. The purpose of this study is to create an online distributor website to make it easier for the public to find savings in their household and business raw material expenses. In this research, the development of the website system uses the Scrum method which is part of the agile method which can produce good quality software according to user desires. This method has a flexible nature that can be applied to the development of the Sembakoqu system by implementing a computerized payment and reporting system. The testing phase used on this website uses the blackbox method by emphasizing testing on functionality. For application development suggestions that can be carried out in further research, namely the system can be developed into a mobile application, so that consumers can order products on their smartphone devices.